(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Objective: A prospective evaluation of clinical outcome of patients with acetabular fractures involving both columns was done in King Edward Medical University/ Mayo Hospital. All patients were operated by a single posterior approach, directly reducing the posterior wall and column and indirectly reducing the anterior column. The aim was to evaluate the efficacy of this single approach. Material and Method: 19 adult patients (15 male and 4 female) presenting in the accident and emergency department of Mayo Hospital from December 2011 to June 2013 having acetabular fracture involving both the anterior and posterior column falling in E and G group of Judet classification, were included in the study. All patients were operated within 7 days of injury by a single operating team. Open reduction and internal fixation with reconstruction plate and cortical screws was done by exposing and reducing the posterior acetabular column through Kocker Lengenbeck approach. Additional lag screw was used to stabilze anterior column after indirect reduction, digital palpation through the greater sciatic notch and confirmed with C arm images. Patients were followed up 6 months and functional outcome was evaluated after the end of the follow up period using Harris Hip Score and the results were analyzed. Result: Majority of the patients 14 out of 19 had Harris Hip score more than 90 after 6 months of the operative management. Conclusion: It issuggestedthat acetabular fractures involving both the acetabular columns, in Letournel and Judet type E and G, can be managed by a single posterior approach. It is associated with good clinical outcome and lesser soft tissue complications.